2009
DOI: 10.1073/pnas.0904519106
|View full text |Cite
|
Sign up to set email alerts
|

Abcb10 physically interacts with mitoferrin-1 (Slc25a37) to enhance its stability and function in the erythroid mitochondria

Abstract: Mitoferrin-1 (Mfrn1; Slc25a37), a member of the solute carrier family localized in the mitochondrial inner membrane, functions as an essential iron importer for the synthesis of mitochondrial heme and iron-sulfur clusters in erythroblasts. The biochemistry of Mfrn1-mediated iron transport into the mitochondria, however, is poorly understood. Here, we used the strategy of in vivo epitope-tagging affinity purification and mass spectrometry to investigate Mfrn1-mediated mitochondrial iron homeostasis. Abcb10, a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
192
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 196 publications
(196 citation statements)
references
References 38 publications
3
192
0
1
Order By: Relevance
“…6 Porin (Calbiochem, San Diego, CA, USA) and a-actin (Novus Biologicals, Littleton, CO, USA) antibodies were used according to manufacturer's instruction. Mfrn1 and BCL-xL (Cell Signalling, Danvers, MA, USA) antibodies were used as previously described 10,23,24 (Supplementary Figure S1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Porin (Calbiochem, San Diego, CA, USA) and a-actin (Novus Biologicals, Littleton, CO, USA) antibodies were used according to manufacturer's instruction. Mfrn1 and BCL-xL (Cell Signalling, Danvers, MA, USA) antibodies were used as previously described 10,23,24 (Supplementary Figure S1).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ABC-me (ABCB10) has been demonstrated to be required for maximal (not basal) iron import into mitochondria during in vitro erythroid differentiation, as it stabilizes the iron importer mitoferrin 1 (Mfrn1). 10 The mitochondrial topology of ABC-me transporter makes it a likely candidate as a novel exporter having a role in mitochondria detoxification and/or regulating the compartmentalization of heme biosynthesis intermediates between mitochondria and cytosol. Finely tuned compartmentalization and proper mitochondrial function are not only relevant for the rates of heme production but also are essential for cell viability, as accumulation of heme intermediates or regulators of their production in cytosol and/or mitochondria can lead to oxidative stress and toxicity.…”
mentioning
confidence: 99%
“…SLC25A37 (Mitoferrin-1; Mfrn1), a member of the solute carrier family localized in the mitochondrial inner membrane, functions as an essential iron importer for the synthesis of mitochondrial heme and iron-sulfur clusters in erythroblasts. [25] There have been no studies about genetic polymorphisms of SLC25A37 to date. In this study, minor allele homozygotes (G) of rs7830129 of SLC25A37 might be associated (P = 4.141x10 -4 , in recessive model; Table 5) with increased absorption of simvastatin.…”
Section: Discussionmentioning
confidence: 99%
“…A study suggested that ABCB10 might mediate this translocating event [60]. However, other biochemical and genetic studies indicate that ABCB10 is more likely to be involved in the final step of heme synthesis, as discussed above [59,61].…”
Section: Transport Of Heme Synthesis Intermediatesmentioning
confidence: 98%